Encyclopedia of Native American religions : an introduction - Hirschfelder, Arlene B.; Molin, Paulette Fairbanks (New York : Facts on File, 2000)
"Encyclopedia of Native American Religions is a guide to the rich spiritual traditions and practices of Native Americans in the United States and Canada. Included are more than 1,200 entries, alphabetically arranged and fully cross-referenced. Long regarded as quaint curiosities or exotic pagan rites, the religious practices of Native Americans make up a rich, enduring legacy deserving of a place among the great spiritual traditions. Encyclopedia of Native American Religions is a comprehensive resource to these traditions and practices and accords them the respect, status, and attention they deserve." "In this edition, new or updated information has been included on such topics as: national and state legislation, such as the Native American Church Bill, which allows the religious use of peyote, and the Religious Freedom Restoration Act; religious rights in the military; sacred sites; sacred use of tobacco; and court cases involving the participation of non-Indians in Native American religious ceremonies, such as the Sun Dance."--Jacket.
Includes bibliographical references (p. 349-363)-and indexes.
Keywords: Indians of North America -- Religion -- Encyclopedias; Indians of North America -- Rites and ceremonies -- Encyclopedias; Encyclopedias